2018
DOI: 10.1128/aac.00853-18
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Aminoglycoside Susceptibility Identify a Novel Function of KsgA To Secure Translational Fidelity during Antibiotic Stress

Abstract: Antibiotic resistance has become a global crisis. Studies on the mechanism of bacterial tolerance to antibiotics will not only increase our conceptual understanding of bacterial death but also provide potential targets for novel inhibitors. We screened a mutant library containing a full set of in-frame deletion mutants of K-12 and identified 140 genes that possibly contribute to gentamicin tolerance. The deletion of increased the inhibition and killing potency against mid-log-phase bacteria by aminoglycosides.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…Thus, colistin might be a good candidate for combinational therapy with β-lactam antibiotics to treat A. baumannii infection. This result is also consistent with our previous studies that targeting bacterial persistence or tolerance could highly enhance the antibiotic treatment [27,57].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, colistin might be a good candidate for combinational therapy with β-lactam antibiotics to treat A. baumannii infection. This result is also consistent with our previous studies that targeting bacterial persistence or tolerance could highly enhance the antibiotic treatment [27,57].…”
Section: Discussionsupporting
confidence: 93%
“…The bacterial killing was performed as described previously [27] and a detailed protocol is provided in supplementary experimental procedures.…”
Section: Isolation Of Persisters and Bacterial Killing Assaymentioning
confidence: 99%
“…By contrast, bacteria lacking KsgA, the methyltransferase responsible for dimethylation of both nucleotides, become highly susceptible to other antibiotics including aminoglycosides and macrolides Phunpruch et al, 2013;Zou et al, 2018). In the present structure, m 6 2A1519 is singly-methylated whereas m 6 2A1518 is fully methylated (Figure 1-figure supplement 5).…”
Section: Post-translational and Post-transcriptional Modifications Inmentioning
confidence: 65%
“…The most prevalent aminoglycoside resistance gene, aph(6)-Ic, is one of three resistance genes present in the composite transposon Tn5, which is found in Gram-negative bacteria (Steiniger-White et al, 2004). The ksgA gene, which confers resistance to kasugamycin (Zou et al, 2018), was also found in seven isolates. Genes ant(3")-Ia, aph(6)-Id and aph(3')-IIc as well as rpsL mutations, known to be responsible for streptomycin resistance (Ramirez and Tolmasky, 2010), were also found in these isolates ( Supplementary Table S3).…”
Section: Resistance Determinantsmentioning
confidence: 99%